Knee Pads Do Not Affect Physical Performance in Young Female Volleyball Players - Anja Lazić; Milovan Bratić; Stevan Stamenković; Slobodan Andrašić; Nenad Stojiljković; Nebojša Trajković (MDPI AG, 2021)
Knee pads have become increasingly popular among volleyball players. Given the fact high-intensity activities that are crucial to successfully playing this sport lead to an increased risk of a knee injury, the primary use of knee pads is to prevent potential injury. However, no research has been carried out to explain the effects of knee pads on the most important physical abilities in volleyball players, thus directly affecting performance. This study was undertaken to determine the effects of knee pads on the explosive power of the lower extremities, linear speed, and agility in young female volleyball players. In two separated sessions, 84 female volleyball players (age: 14.83 ± 0.72 years; height: 163.19 ± 8.38 cm; body mass: 53.64 ± 10.42 kg; VE: 5.30 ± 3.39 years) completed squat jumps (SJ), countermovement jumps (CMJ) with and without arm swing, linear sprints at 5-m and 10-m, modified t-test, and 5-10-5 shuttle test. Data analyses included descriptive statistics, paired sample T-tests and use of effect size (ES). There was no statistical difference between the two conditions for SJ (p = 0.156; ES = 0.18), CMJ (p = 0.817; ES = 0.03), CMJ with arm swing (p = 0.194; ES = 0.14), linear sprint at 5 m (p = 0.789; ES = 0.03) and 10 m (p = 0.907; ES = −0.01), modified t-test (p = 0.284; ES = 0.13), and 5-10-5 shuttle test (p = 0.144; ES = 0.19). Wearing knee pads has neither an inhibitory nor positive effects on explosive power of the lower extremities, linear speed, and agility in young female volleyball players.